On-shelf Streptokinse EnsuRes More Favorable In-hospital Outcome after Acute STEMI (OSTRIC trial) - A Single Centre Randomized Controlled Trial (Bangladesh Heart Journal, 2018)
Introduction: The burden of CAD is increasing at a greater rate in South Asia than in any other region globally. Among them acute ST elevation myocardial infarction (STEMI) is one of the leading causes of death and disability. Major aspect of treatment of acute STEMI is reperfusion of the infarct related artery. Delay in reperfusion is associated with higher mortality and morbidity rates. While primary percutaneous coronary intervention (PCI) is the preferred mode of reperfusion, only few patients can get this form of reperfusion within recommended timelines. On the other hand, thrombolysis is easily available, economical and evaluated in several clinical studies. Thrombolysis is an important reperfusion strategy, especially when primary PCI cannot be offered to STEMI patients, with a time dependent fashion.Methods: This randomized controlled trial was conducted in the department of Cardiology of National Institute of Cardiovascular Diseases since January 2016 to June 2018. Objective of the study was to find out the outcomes of acute STEMI patients after getting on-shelve or purchased Streptokinase (STK). Initially there was no free supply of STK in our hospital as it is an expensive drug, later on fund was arranged and STK was made available at free of cost by the hospital authority. Total 300 patients fulfilling inclusion and exclusion criteria were included in the study. Group I: 150 patients received on-shelf STK when it was made free by the authority and Group II: 150 patients received purchased STK when it was not available at free of cost. Study populations were analyzed for LVF, Cardiogenic shock, MACE (re-infarction, stroke and death) and duration of hospital stay.Results: The mean age of the study population in group I and II were 53.88 ± 14.51 vs. 57.18 ± 15.28 years (p= 0.46). Mean door to injection time in group I and II were 25.51 ± 7.9 vs. 70.36 ± 16.6 minutes (p=